Open Polar: A mid-way report toward a unique service - Abu-Alam, Tamer (Ravnetrykk, 2020)
Data from the Polar Regions are of critical importance to modern research and decision makers. Regardless of their disciplinary and institutional affiliations, researchers rely heavily on the comparison of existing data with new data sets to assess changes that are taking effect. However, in a recent survey of 113 major polar data providers, we found that an estimated 60% of the existing polar research data is unfindable through common search engines and can only be accessed through institutional webpages. This raises an awareness sign of the need of the scientific community to harvest different metadata related to the Polar Regions and collect it in a homogenous, seamless database and making this database available to researchers, students and publics through one search platform. This contribution describes the progress in an ongoing project, Open Polar, started in 2019 at UiT The Arctic University of Norway. The project aims to collect metadata about all the open-access research data, articles and other scholarly documents related to the Polar Regions in a homogenous and seamless database. During the first six months of the project, the beta version of the user-interface was established, with a search by map and an advanced search function. An extensive geo-database that includes thousands of polar locations and their geographic information was collected from different sources. The geo-database together with a list of keywords (i.e. on sources, indigenous peoples, languages and other polar-related keywords) will be used in the filtration process. A Reference Board was formed, and the first board meeting took place in April 2020. The geographic definition of “Polar Regions” was defined in order to include most of the current geographic definitions of “Arctic”. The project is still facing some challenges that include for example integration with non-standard data sources who do not use Dublin Core Metadata schema, or are not harvestable through the Open Access Initiative’s standard protocol for harvesting (OAI-PMH).